2021
DOI: 10.1177/0972262921990981
|View full text |Cite
|
Sign up to set email alerts
|

Do Lower Foreign Flows and Higher Domestic Flows Reduce Indian Equity Market Volatility?

Abstract: This study examines the relationship that both domestic and foreign institutional net equity flows have with the India stock markets. The motivation behind is the study to examine whether increased net equity investments from domestic institutional investors has reduced the influence of foreign equity flows on the Indian stock market volatility. Our results indicate that only during periods in which domestic equity inflows surpass foreign flows by a significant margin, as seen during 2015–2018, is the Indian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In addition to this, it is found that the financial and economic time series usually have time-varying volatility that must be modelled exclusively (Bollerslev, 1986;Bollerslev et al, 1992;Engle, 1982); and hence, ARCH and GARCH family of models are used to estimate volatility of such time series. Literature is also replete with the instances of the use of the GARCH family of models to estimate volatility in such time series (Aggarwal et al, 2020(Aggarwal et al, , 2021aKarmakar, 2005;Rastogi, 2011Rastogi, , 2014Rastogi and Srivastava, 2011). Nevertheless, over the period, it is also witnessed that to model the co-movement of the time series, the cointegration can be used (Rastogi, 2013;Engle and Granger, 1987;Johansen, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, it is found that the financial and economic time series usually have time-varying volatility that must be modelled exclusively (Bollerslev, 1986;Bollerslev et al, 1992;Engle, 1982); and hence, ARCH and GARCH family of models are used to estimate volatility of such time series. Literature is also replete with the instances of the use of the GARCH family of models to estimate volatility in such time series (Aggarwal et al, 2020(Aggarwal et al, , 2021aKarmakar, 2005;Rastogi, 2011Rastogi, , 2014Rastogi and Srivastava, 2011). Nevertheless, over the period, it is also witnessed that to model the co-movement of the time series, the cointegration can be used (Rastogi, 2013;Engle and Granger, 1987;Johansen, 1991).…”
Section: Methodsmentioning
confidence: 99%